2012
DOI: 10.1148/rg.325125002
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Necrosis in the Brain: Imaging Features and Differentiation from Tumor Recurrence

Abstract: Radiation necrosis in the brain commonly occurs in three distinct clinical scenarios, namely, radiation therapy for head and neck malignancy or intracranial extraaxial tumor, stereotactic radiation therapy (including radiosurgery) for brain metastasis, and radiation therapy for primary brain tumors. Knowledge of the radiation treatment plan, amount of brain tissue included in the radiation port, type of radiation, location of the primary malignancy, and amount of time elapsed since radiation therapy is extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(167 citation statements)
references
References 19 publications
5
156
0
2
Order By: Relevance
“…Lastly, a short follow-up duration could account for the lack of RN observed. However, median survival time amongst the five survivors in the present study was 23.3 months, which falls within the 2 -23 months period where RN is most likely observed [31]. For instance, Floyd, et al [38] reported survival of patients with brain necrosis at 23, 20, and nine months.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Lastly, a short follow-up duration could account for the lack of RN observed. However, median survival time amongst the five survivors in the present study was 23.3 months, which falls within the 2 -23 months period where RN is most likely observed [31]. For instance, Floyd, et al [38] reported survival of patients with brain necrosis at 23, 20, and nine months.…”
Section: Discussionsupporting
confidence: 46%
“…RN can be seen between two to 23 months following radiation therapy [31]. RN was assessed subjectively using advanced MR imaging including diffusion-weighted imaging (DWI), apparent diffusion coefficient (ADC) mapping, MR spectroscopy, and PET.…”
Section: Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk increases with the radiation dose given as well as the type of radiation and technique used. 16 Given the proximity of the cranial nerves and skull base to the parenchyma, it may be encountered in the setting of treatment for perineural spread (PNS). On imaging, this will present as a focal area of abnormal T2 high signal with central necrosis and peripheral enhancement, predominantly involving white matter (►Fig.…”
Section: Complications Posttreatmentmentioning
confidence: 99%
“…Moreover, it is difficult to ask patients with multiple intracranial [12]. In this study, the patients were diagnosed based on a comprehensive medical history, symptoms, signs, MRI, spectroscopy and positron emission tomography-computed tomography (PET-CT) [13][14][15][16][17][18][19][20]. MRI or spectroscopy was performed first, and then, PET-CT was performed as needed for ambivalent diagnoses.…”
Section: Clinical Diagnostic Criteria For Brain Necrosismentioning
confidence: 99%